Tensile behaviour of a basalt TRM strengthening system: Influence of mortar and reinforcing textile ratios. (1st December 2017) - Caggegi, Carmelo; Lanoye, Emma; Djama, Khaled; Bassil, Antoine; Gabor, Aron
Abstract: The use of textile reinforced mortar (TRM) composites is considered a suitable solution to strengthen historical masonry structures. Specifically, TRM composites are characterised by a textile embedded in a mortar matrix. In the present work, we propose a thorough experimental analysis of basalt textile reinforced mortar. Four series of tensile tests were carried out on specimens characterised by three different basalt textile reinforcing ratio and two different kinds of mortar (usual gauged mortar and thixotropic mortar with additives). The use of digital image correlation facilitated detailed description of the displacement fields and the crack pattern during the tests. The comparison between the results of each series allowed us to evaluate the influence of the different parameters on the behaviour of the analysed TRM and to obtain useful information regarding the strengthening design.